Automatización de un sistema de motores trifásicos con inversión de giro bajo el mando de un programador lógico controlable PCL. - Cisneros Santos, Darwin Rolando (2010)
At the present time the changes that take place in the systems of automatic control are more and more notorious, it is so many of the factories, residences and local commercial, they make use of these systems of automatic control allowing a bigger efficiency and effectiveness in the moment of their application. Not a long time ago the process of industrial control was carried out it with electromechanical devices as contactores and relés like only control implements. The problem of the relés and the contactores are that when the production requirements change, he/she also makes it the control system. This is expensive when the changes are frequent. Since the relés and contactores are electromechanical devices that possess a certain lifespan, they require a planned strict maintenance. On the other hand, in occasions they should be carried out connections between several relés and contactores, what implies an enormous design effort and maintenance. The formless present has as purpose to develop the didactic guides so that the students develop the necessary practices for the automation of a system of motors trifásicos with turn investment under the control of a logical controllable programmer. The logical controllable programmer PLC has been implemented in the one that to make industrial, allowing to control in form continues the speed of the motors monofásicos and asynchronous trifásicos. Modern PLC is based on micro controllers, in modules of power with automatic protection functions and in intelligent control units. In this context one can affirm that the present practical work, applied to the control of motors trifásicos will contribute in the academic formation, the students' of the Career of Technology técnic, práctical in Electricity and likewise it serves from support to the Career of Electromechanical Engineering.